Analisa Kekuatan Pada Sambungan Las Baja St 37 Dengan Pengelasan Smaw Di Dalam Air Tawar , Air Laut Dan Di Darat - Prasetyawan, Tommy, Agus Dwi Anggono, ST, M.Eng, Ph.D, Agus Yulianto, ST, MT (2017)
The scope of use modern welding techniques are in ship building, construction of offshore oil rigs, pipelines channeling of natural gas, pressure vessel, and etc. Steel construction of offshore oil rigs should be able to stand more than 25 years. Sometimes, the construction oil platform have unexpected damage, which has required to be repaired. Underwater welding was selected from many repairing technique because of the easier process and low cost investment. Therefore, the methods were developed rapidly and many researchers included in the improvement of underwater welding strength and weld joint quality. The objective of the study are to determine the tensile strength, hardness, and micro structure of underwater welding. The material used in the study was ST 37 steel. The welding process were performed in underwater of fresh water, sea water and on the ground. The result of this study was shown the highest tensile strength of 373,13 MPa. It was delivered by the welding process under sea water. The strain value was 15,99 %. The underwater welding of fresh water given the lowest tensile strength of 323,56 MPa with the strain of 15,06 %. Hardness test of weld zone of under fresh water welding was given the highest hardness of 253,4 VHN . while the lowest hardness was got from the ground welding process in the value of 184,3VHN. The result were supported by the views of weld zone photo micro. It was seen smaller grain size of under of under fresh water welding compared to the ground welding specimen.